De l'art de se situer. Entre héritage et prescription, éléments pour une analyse pragmatique des identités professionnelles des enseignants spécialisés de la musique - Joris Cintero
After four decades of pedagogical and structural evolutions, French music schools gather today a very large and different range of disciplines, teaching visions and pedagogical methods. This evolution mixes a huge pedagogical legacy and a framework of plural and reformist instructions that blurs the usual framework in which the music teacher's job is traditionally defined. As a tentative to understand those changes, this article examines how music teachers identify themselves to the pedagogical legacy of the French conservatoire and to the various instructions they are given by the different layers of French state. It shows how important those elements are in the building of professional identities as it exposes the major importance of local cultural policies in this process.